2013
DOI: 10.1074/jbc.m112.436113
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Anti-apoptotic E3 Ubiquitin Ligase That Ubiquitinates Antagonists of Inhibitor of Apoptosis Proteins SMAC, HtrA2, and ARTS

Abstract: Background:Mitochondrial proapoptotic proteins such as SMAC, HtrA2, and ARTS promote apoptosis by antagonizing the inhibitor of apoptosis proteins (IAPs). Results: A novel anti-apoptotic E3 ubiquitin ligase, AREL1 was cloned and identified to interact with and ubiquitinate the IAP antagonists. Conclusion: AREL1 inhibits apoptosis through ubiquitinating the cytosolic IAP antagonists. Significance: AREL1-mediated degradation of IAP antagonists represents a new anti-apoptotic signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…Although the panel was expressed less frequently in ADC than the other 2 tumor types, the combined sensitivity of the panel and conventional cytology was significantly better than cytology alone ( P< .00001) in detecting ADCs in bronchial brushings. To our knowledge, KIAA1522 and KIAA0317 are uncharacterized proteins that were screened from many high‐throughput methods, and only a few functional studies were reported . In our current study, the expression status of the proteins and their correlation with clinicopathologic features were evaluated in bronchial brushings.…”
Section: Discussionmentioning
confidence: 99%
“…Although the panel was expressed less frequently in ADC than the other 2 tumor types, the combined sensitivity of the panel and conventional cytology was significantly better than cytology alone ( P< .00001) in detecting ADCs in bronchial brushings. To our knowledge, KIAA1522 and KIAA0317 are uncharacterized proteins that were screened from many high‐throughput methods, and only a few functional studies were reported . In our current study, the expression status of the proteins and their correlation with clinicopathologic features were evaluated in bronchial brushings.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, we identified a shift from cytosine methylation towards hydroxymethylation, a modification commonly associated with increased gene expression activity, at the cg08753407 probe mapping to the AREL1 gene in MSA patients. The AREL1 gene codes for an E3 ubiquitin ligase involved in protein ubiquitination and degradation [53]. Further, E3 ubiquitin ligases mark proteins for degradation in the proteasome which is necessary for antigen presentation through MHC Class I complexes (reviewed by Loureiro & Ploegh [54]).…”
Section: Discussionmentioning
confidence: 99%
“…2a, b), two probes showed a mean difference > 5% with one probe mapping to AREL1 (cg08753407, change (Δ) in methylation (β) = − 9.1%, P = 1.47E-07; Fig. 2b) belonging to the E3 ubiquitin ligase family [53] necessary for antigen presentation [54]. Hence, this change in methylation indicates an immune activation in MSA patients.…”
Section: Arel1 Presents a Shift From Cytosine Methylation To Cytosinementioning
confidence: 95%
“…cIAP1 was also reported to inhibit apoptosis by targeting the downstream of cytochrome c , via the interaction with activated caspase-9 and thus disrupting caspase-9 and the downstream activation of procaspase-3 (Burke, Smith, & Smith, 2010). These mitochondrial IAP antagonists are in turn ubiquitinated in the cytosol of apoptosis-stimulated cells by AREL1 E3 ligase to inhibit apoptosis (Kim et al, 2013). …”
Section: Dubs In Regulation Of Apoptosis Pathways In Cancersmentioning
confidence: 99%